Shedding of host autophagic proteins from the parasitophorous vacuolar membrane of Plasmodium berghei - Carolina Agop-Nersesian (Nature Portfolio, 2017)
Abstract The hepatic stage of the malaria parasite Plasmodium is accompanied by an autophagy-mediated host response directly targeting the parasitophorous vacuolar membrane (PVM) harbouring the parasite. Removal of the PVM-associated autophagic proteins such as ubiquitin, p62, and LC3 correlates with parasite survival. Yet, it is unclear how Plasmodium avoids the deleterious effects of selective autophagy. Here we show that parasites trap host autophagic factors in the tubovesicular network (TVN), an expansion of the PVM into the host cytoplasm. In proliferating parasites, PVM-associated LC3 becomes immediately redirected into the TVN, where it accumulates distally from the parasite’s replicative centre. Finally, the host factors are shed as vesicles into the host cytoplasm. This strategy may enable the parasite to balance the benefits of the enhanced host catabolic activity with the risk of being eliminated by the cell’s cytosolic immune defence.